Analisis Nilai Tambah Jahe Pada UMKM Eufraino UD Makaaruien Di Kota Manado - Ponto, Angly Mariani; Rumagit, Grace Adonia Josephine; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the added value of ginger in herbal drinks Eufraino UD Makaaruien in Manado City. This research was conducted from September to October 2023. The data used were primary data and secondary data. Primary data was obtained by direct inter-view with the owner of UD Makaaruien and employees (labor) as well as direct observation at the research site. Secondary data is obtained from various literature related to this research. The data taken in this study is data in August 2023. The results showed that the added value of ginger in Eufraino herbal drinks UD Makaaruien in August 2023 for red ginger instant juice prod-ucts with 15 kg of ginger amounted to Rp 928,477 or Rp 61,898.5 per kg or 618.985%. Then for mangosteen 3 in 1 products with (2 kg of ginger, 3 kg of mangosteen and 2 kg of temulawak) amounting to IDR 483,727 or for 1 kg of ginger can provide added value of IDR 59,467.5 or 594.675%.